Electronic Word of Mouth and Promotion in Driving Repurchase Intention through Customer Satisfaction in the Hospitality Industry - Yanti Nirmala (PT FORMOSA CENDEKIA GLOBAL, 2026)
This study examines the influence of electronic word of mouth (e-WOM) and promotion on customer satisfaction and revisit intention at Ibis Styles Bekasi Hotel. The study focuses on guests who have stayed at the hotel at least twice, with data collected from 120 respondents using incidental sampling. Questionnaires were distributed between October and December 2025. Data analysis was conducted using Partial Least Squares Structural Equation Modelling (PLS-SEM) with SmartPLS. The results reveal that promotion and revisit intention have a positive and significant effect on customer satisfaction. Furthermore, e-WOM, promotion, and customer satisfaction positively and directly influence revisit intention. However, e-WOM is found to have an adverse direct effect on customer satisfaction. In terms of mediation, customer satisfaction significantly mediates the relationship between promotion and revisit intention, while it does not mediate the relationship between e-WOM and revisit intention. These findings highlight the critical roles of promotional strategies and customer satisfaction in enhancing revisit intention in the hospitality industry, while suggesting that not all forms of e-WOM positively affect customer satisfaction.